A study on the efficacy of topical 10% potassium hydroxide in the treatment of Molluscum contagiosum - Fiona Frida Sequeira; Nanda Kishore Bala; Ganesh Kamath Hundi; Jacintha Martis (Wolters Kluwer Medknow Publications, 2016)
Context: Molluscum contagiosum (MC) is a highly contagious, nonsevere pediatric viral infection, with the current treatment modalities having negative aesthetic and psychological effects. Aims: To study the efficacy of 10% potassium hydroxide (KOH) solution in the treatment of MC. Materials and Methods: This prospective, open-labeled study was conducted in 40 patients who were clinically diagnosed with MC to know the efficacy of 10% KOH over a period of 18 months attending the outpatient department of Father Muller Medical College Hospital, Mangalore, Karnataka, India. Results: All the 40 patients (100%) showed complete clearance of lesions at the end of 4 weeks. The maximum number of patients belonged to the age group of less than 5 years, with the face being the most common site. Conclusion: Therapy with 10% KOH solution was found to be safe and effective in the treatment of MC.